Change in the Prevalences and Risk Factors of Atrophic Gastritis and Intestinal Metaplasia in Korea: Multicenter Clinical Trials - Young-Jae Hwang; Nayoung Kim; Sung Eun Kim; Gwang Ho Baik; Ju Yup Lee; Kyung Sik Park; Young-Eun Joo; Dae-Seong Myung; Hyeon Ju Kim; Hyun Joo Song; Heung Up Kim; Kwangwoo Nam; et al. (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims: The aim of this study was to analyze the trend of the prevalences of atrophic gastritis (AG) and intestinal metaplasia (IM) from 2011 to 2016∼2017 in Korea. And, the risk factors of AG and IM were compared between 2011 and 2016∼2017. Materials and Methods: A total of 4,023 subjects in 2011 and 2,506 subjects in 2016∼2017 were enrolled. AG and IM were diagnosed on the basis of endoscopic findings. Multivariate analysis was performed for risk factors of AG and IM. Seventeen factors were analyzed. Results: The seroprevalence of Helicobacter pylori decreased from 2011 (59.8%; 2,407/4,023) to 2016∼2017 (51.6%; 1,293/2,506; P＜ 0.001). The prevalence of AG decreased from 2011 to 2016∼2017 (P=0.018), but that of IM increased (P＜ 0.001). The risk factors of AG in 2011 were male sex, old age, H. pylori immuoglobulin G (IgG) positivity, family history of gastric cancer (GC), and high-salt diet. For IM in 2011, the risk factors were male sex, old age, H. pylori IgG positivity, and family history of GC. Risk factors of AG in 2016∼2017 were old age, H. pylori IgG positivity, and country of residence. For IM in 2016∼2017, the risk factors were male sex, old age, family history of GC, high fasting glucose level (≥126 mg/dL), H. pylori IgG positivity, and low income level. Conclusions: The difference in prevalence trends of AG and IM between 2016∼2017 and 2011 could be the result of the different risk factors of AG and IM, such as decreased prevalence of H. pylori infection.